DAMPAK SISTEM DISTRIBUSI LPG 3 KG TERHADAP KESEJAHTERAAN MASYARAKAT DI INDONESIA DALAM PRESPEKTIF ISLAM: KONSEP KESEJAHTERAAN MENURUT ISLAM - Aulia Fauziah; Nurlaila Juniawati; Lina Marlina (UQUDUNA: Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the impact of the 3 kg LPG distribution system on people's welfare in Indonesia using an Islamic economic perspective. 3 kg LPG is an energy subsidy intended for low-income people. However, in its implementation, LPG distribution often misses the target, causes scarcity, and triggers social inequality. Through a qualitative approach with literature study and policy analysis, this paper evaluates how the LPG distribution system affects the social and economic aspects of society and reviews its compatibility with the principles of justice, benefit and equitable distribution in Islam. The results of the study show that the inaccuracy of the 3 kg LPG distribution system can hinder the achievement of fair and equitable welfare as taught in Islamic teachings. Therefore, it is necessary to reform the distribution system based on the values of social justice and collective responsibility to realize sustainable welfare for the entire community.